Transmission eigenvalue distributions in highly conductive molecular junctions - Bergfield, Justin P.; Barr, Joshua D.; Stafford, Charles A. (Beilstein Journal of Nanotechnology, 2012)
Background: The transport through a quantum-scale device may be uniquely characterized by its transmission eigenvalues τn. Recently, highly conductive single-molecule junctions (SMJ) with multiple transport channels (i.e., several τn > 0) have been formed from benzene molecules between Pt electrodes. Transport through these multichannel SMJs is a probe of both the bonding properties at the lead–molecule interface and of the molecular symmetry.Results: We use a many-body theory that properly describes the complementary wave–particle nature of the electron to investigate transport in an ensemble of Pt–benzene–Pt junctions. We utilize an effective-field theory of interacting π-electrons to accurately model the electrostatic influence of the leads, and we develop an ab initio tunneling model to describe the details of the lead–molecule bonding over an ensemble of junction geometries. We also develop a simple decomposition of transmission eigenchannels into molecular resonances based on the isolated resonance approximation, which helps to illustrate the workings of our many-body theory, and facilitates unambiguous interpretation of transmission spectra.Conclusion: We confirm that Pt–benzene–Pt junctions have two dominant transmission channels, with only a small contribution from a third channel with τn << 1. In addition, we demonstrate that the isolated resonance approximation is extremely accurate and determine that transport occurs predominantly via the HOMO orbital in Pt–benzene–Pt junctions. Finally, we show that the transport occurs in a lead–molecule coupling regime where the charge carriers are both particle-like and wave-like simultaneously, requiring a many-body description.
Keywords: benzene–platinum junction; effective-field theory; isolated-resonance approximation; lead–molecule interface; many-body theory; multichannel; quantum transport; single-molecule junction; transmission eigenchannels

(untitled) - Scheer, E.; Agraït, N.; Cuevas, J. C.; Levy Yeyati, A.; Ludoph, B.; Martín-Rodero, A.; Rubio Bollinger, G.; van Ruitenbeek, J. M.; Urbina, C. (Nature, 1998)

(untitled) - Bergfield, J. P.; Barr, J. D.; Stafford, C. A. (ACS Nano, 2011)

(untitled) - Kiguchi, M.; Tal, O.; Wohlthat, S.; Pauly, F.; Krieger, M.; Djukic, D.; Cuevas, J. C.; van Ruitenbeek, J. M. (Phys. Rev. Lett., 2008)

Electronic Transport in Mesoscopic Systems - Datta, S. (Cambridge University Press, 1995)

(untitled) - Bergfield, J. P.; Stafford, C. A. (Phys. Rev. B, 2009)

(untitled) - Toher, C.; Filippetti, A.; Sanvito, S.; Burke, K. (Phys. Rev. Lett., 2005)

(untitled) - Koentopp, M.; Burke, K.; Evers, F. (Phys. Rev. B, 2006)

(untitled) - Muralidharan, B.; Ghosh, A. W.; Datta, S. (Phys. Rev. B, 2006)

(untitled) - Geskin, V.; Stadler, R.; Cornil, J. (Phys. Rev. B, 2009)

(untitled) - Bergfield, J. P.; Jacquod, P.; Stafford, C. A. (Phys. Rev. B, 2010)

(untitled) - Bergfield, J. P.; Solomon, G. C.; Stafford, C. A.; Ratner, M. A. (Nano Lett., 2011)

(untitled) - Castleton, C. W. M.; Barford, W. (J. Chem. Phys., 2002)

(untitled) - Djukic, D.; van Ruitenbeek, J. M. (Nano Lett., 2006)

(untitled) - Solomon, G. C.; Gagliardi, A.; Pecchia, A.; Frauenheim, T.; Di Carlo, A.; Reimers, J. R.; Hush, N. S. (Nano Lett., 2006)

(untitled) - Kovac, B.; Mohraz, M.; Heilbronner, E.; Boekelheide, V.; Hopf, H. (J. Am. Chem. Soc., 1980)

(untitled) - Sell, J. A.; Kuppermann, A. (Chem. Phys., 1978)

(untitled) - Kobayoshi, T. (Phys. Lett. A, 1978)

(untitled) - Schmidt, W. (J. Chem. Phys., 1977)

(untitled) - Baltzer, P.; Karlsson, L.; Wannberg, B.; Öhrwall, G.; Holland, D. M. P.; MacDonald, M. A.; Hayes, M. A.; von Niessen, W. (Chem. Phys., 1997)

(untitled) - Howell, J. O.; Goncalves, J. M.; Amatore, C.; Klasinc, L.; Wightman, R. M.; Kochi, J. K. (J. Am. Chem. Soc., 1984)

(untitled) - Burrow, P. D.; Michejda, J. A.; Jordan, K. D. (J. Chem. Phys., 1987)

CRC Handbook of Chemistry and Physics - Lide, D. R. (CRC Press, 2005)

Introduction to Scanning Tunneling Microscopy - Chen, C. J. (Oxford University Press, 1993)

(untitled) - Kleber, R. Z. (Phys. A: Hadrons Nucl., 1973)

Introduction to solid state physics - Kittel, C. (John Wiley and Sons, Inc., 1976)

(untitled) - Cruz, M. T. d. M.; Carneiro, J. W. d. M.; Aranda, D. A. G.; Bühl, M. (J. Phys. Chem. C, 2007)

(untitled) - Morin, C.; Simon, D.; Sautet, P. (J. Phys. Chem. B, 2003)

(untitled) - Saeys, M.; Reyniers, M.-F.; Marin, G. B.; Neurock, M. (J. Phys. Chem. B, 2002)

(untitled) - Heurich, J.; Cuevas, J. C.; Wenzel, W.; Schön, G. (Phys. Rev. Lett., 2002)

(untitled) - Levitov, L. S.; Lee, H.; Lesovik, G. B. (J. Math. Phys., 1996)

(untitled) - Levitov, L. S.; Lesovik, G. B. (JETP Lett., 1993)
http://adsabs.harvard.edu/abs/1993JETPL..58..230L

(untitled) - Büttiker, M. (Phys. Rev. Lett., 1990)